PENGARUH AUDIT FEE, NON-AUDIT SERVICES DAN AUDIT TENURE PADA INDEPENDENSI AUDITOR - Aditama Manuaba, Ida Bagus Ananta; Utama, I Made Karya (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2016)
The purpose of this study was to determine the effect of audit fees, non-audit services and audit tenure on auditor independence. This research was conducted at the public accounting firm in the area of Bali. Samples in this study of 73 respondents to the sampling technique used was purposive sampling. The data collection method used is the method of questionnaires and documentation. Data analysis technique used is the technique of multiple linear regression analysis. Based on the results of research by distributing questionnaires to 44 respondents, it can be concluded that the audit fee and significant effect on the independence of auditors, the non-audit services and significant influence on the independence of auditors, and audit tenure and significant impact on auditor independence.
Keywords: Audit fee, Non-Audit services, Audit Tenure, Independensi Auditor